PELATIHAN PENYUSUNAN MEDIA AJAR MATEMATIKA BERBASIS PENDEKATAN KONTEKSTUAL BAGI GURU PPWNI KLANG MALAYSIA - Uki Suhendar; Arta Ekayanti; Erika Eka Santi; Afrina Maya Febryanti; Lailatul Magfiroh (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
Learning at PPWNI Klang Malaysia is limited in many ways, one of which is the teaching staff. There are only 2 teachers so the teacher's role is not optimal, especially in the preparation of teaching media. On the other hand, learning mathematics for elementary school students still requires concrete media as a learning tool. Therefore it is necessary to provide training for teachers at PPWNI Klang Malaysia in preparing mathematics teaching media. In the context of efficiency and effectiveness of media preparation, media based on a contextual approach were selected. The output target of this service is an increase in the competence of teachers at PPWNI Klang Malaysia in preparing mathematics teaching media. Held directly at PPWNI Klang Malaysia every working day for a full month. Training is carried out after the implementation of learning in class. Followed by mentoring activities for the development of mathematics teaching media by teachers in groups. The result of this dedication is the increased competence of teachers at PPWNI Klang Malaysia in creating learning media, as evidenced by the media that has been created.